Tax-Favored Retirement Accounts: Are they Efficient in Increasing Savings and Growth? - Hans Fehr; Christian Habermann; Fabian Kindermann (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2006)
The present paper aims to quantify the macroeconomic and welfare effects of taxfavored retirement accounts. Starting from an equilibrium without saving incentives, we introduce such accounts and compute the new transition path and the resulting long-run equilibrium. Since our overlapping-generations model comprises a detailed progressive tax system, borrowing constraints as well as stochastic income risk, we can compare macroeconomic and liquidity effects, tax distortions and the insurance properties of the policy reform. Our simulations indicate that tax-favored retirement accounts as implemented in many OECD countries will have a significant impact on capital accumulation and wage growth in the long run, but only yield insignificant aggregate efficiency changes. While elderly generations are typically hurt by such a reform, young and future generations benefit. Finally, with respect to the intragenerational redistribution, a subsidy system that includes direct bonus payments might be preferred to a system with pure tax deductions.
Keywords: H55; J26; 330; Savings incentives; stochastic general equilibrium model